(untitled) - Wyatt, Rawdon (Cambridge, 2012)
Combines the very best in contemporary classroom practice with stimulating topics aimed at young adults. It is designed to introduce students to the critical thinking required for IELTS and provide strategies and skills to maximise their score in all parts of the test.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Textbooks for foreign speakers,Problems, exercises, etc.,Sách giáo khoa cho người nói tiếng nước ngoài,Câu hỏi, bài tập